Pengaruh Kecemasan Terhadap Konsentrasi Belajar Siswa Dalam Mempersiapkan Ujian Kelulusan Pada Siswa Kelas XII di SMAN 1 Purwosari - K, Khabiba; Kelly, Estalita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Anxiety is one of the psychological factors that can potentially affect students’ study concentration, particularly in the face of stressful situations such as graduation exams. This study aimed to know the influence of anxiety on the study concentration of class XII learners in Public High School 1 Purwosari. This study used a quantitative approach with a correlational design. The population in this study was the entire students of class XII in Negeri High School 1 Purwosari, with a total sample size of 176 students taken using simple random sampling technique. The instruments used in this study were anxiety scale and study concentration scale. Data analysis F value was 43.233 with significance greater than 0.000 due to Sig value. 0.05 then it can be concluded that there is a significant influence between anxiety on study concentration. Thus the hypothesis stating there is an influence between anxiety on concentration of study in learners in Public High School 1 Purwosari is accepted.